Thriving in youth sport: the antecedents and consequences. Issue 2 (4th March 2022) - Kinoshita, Keita; MacIntosh, Eric; Sato, Shintaro
ABSTRACT: Thriving, "a psychological state composed of the joint experience of vitality and learning (Spreitzer, Sutcliffe, Dutton, Sonenshein, & Grant [2005]. A socially embedded model of thriving at work. Organization Science, 16(5), 537–549.)" might offer further insight into the problem of youth sport development research. The purpose of the study was to investigate the mechanisms underlying thriving within a youth sport context. More specifically, the present study considered the perspective of Self-Determination Theory and in particular, how hedonic and eudaimonic motives, as antecedents of thriving, influenced youth athletes' outcomes (i.e., intention to continue sport, subjective well-being in sport, and goal progress), consequences of thriving. 196 youth sport participants answered an online survey. Path analysis was conducted to test our hypotheses. We used the bias-corrected bootstrap procedure to examine the hypothesised indirect effects. Our results showed that both hedonic and eudaimonic motives were positively related to all outcome variables (intention to continue sport, subjective well-being in sport, and goal progress) through both the basic psychological need satisfaction and thriving. Thriving is an important psychological concept that can facilitate youth athletes to acquire important outcomes for youth sport participation.